Decoding the components of dynamics in three‐domain proteins. Issue 7 (9th December 2013) - Maciejewski, Mateusz; Barlow, Paul N.; Tjandra, Nico
Abstract : In this study, we examine the feasibility and limitations of describing the motional behavior of three‐domain proteins in which the domains are linearly connected. In addition to attempting the determination of the internal and overall reorientational correlation times, we investigate the existence of correlations in the motions between the three domains. Since in linearly arranged three‐domain proteins, there are typically no experimental data that can directly report on motional correlation between the first and the third domain, we address this question by dynamics simulations. Two limiting cases occur: (1) for weak repulsive potentials and (2) when strong repulsive potentials are applied between sequential domains. The motions of the terminal domains become correlated in the case of strong interdomain repulsive potentials when these potentials do not allow the angle between the sequential domains to be smaller than about 60°. Using the model‐free (MF) and extended MF formalisms of Lipari and Szabo, we find that the motional behavior can be separated into two components; the first component represents the concerted overall motion of the three domains, and the second describes the independent component of the motion of each individual domain. We find that this division of the motional behavior of the protein is maintained only when their timescales are distinct and can be made when the angles between sequential domains remain between 60° and 160°. In this work, we identify and quantify interdomain motional correlations. © 2013 Wiley Periodicals, Inc. Abstract : The feasibility and limitations of describing the motional behavior of three‐domain proteins in which the domains are linearly connected are studied via Brownian dynamics simulations. Two limiting cases occur: the domain motion is independent when the domains interact via weak potentials, and interdependent when these potentials are strong. Dynamics in three‐domain systems is completely described by model‐free formalism.